The Finnish Diabetes Risk Score (FINDRISC) and increased body weight - Pekar, Joanna; Mazur, Rafał; Kozilewicz, Małgorzata; Jóźwiak, Aleksandra; Olszewska, Anna; Skórzyńska-Dziduszko, Katarzyna (Journal of Medical Science, 2016)
Introduction. The Finnish Diabetes Risk Score (FINDRISC) assesses the 10-year type 2 diabetes risk in adults by identifying individuals with overweight or obesity, inadequate physical activity, poor nutrition, or a family or personal history of hyperglycaemia. Aim. The objective of the study was to analyse the effect of FINDRISC components, particularly overweight/obesity, on the total FINDRISC score of randomly selected individuals. Material and methods. The study was conducted in 2015 on 91 individuals – 45 women and 46 men. We determined FINDRISC score and measured blood pressure twice. The results were analysed in STATISTICA 10 at p < 0.05. Results. Thirty subjects (32.97%) were overweight (BMI 25–29.9 kg/m2) and 12 (13.19%) were obese (BMI >= 30 kg/m2); 25 (27.47%) had high waist circumference (M: 94–102 cm; F: 80–88 cm) and 24 (26.37%) abdominal obesity (M: > 102 cm; F: > 88 cm). Individuals with overweight/obesity, high waist circumference or abdominal obesity had significantly higher FINDRISC scores than those with normal body weight and waist circumference. Obese individuals showed a strong tendency (p = 0.06) towards higher FINDRISC scores than overweight individuals, but no similar difference was noted between high waist circumference and abdominal obesity. Overweight and obese subjects had significantly higher blood pressure, but with no difference between them. Individuals with abdominal obesity, but not those with high waist circumference, had significantly higher blood pressure. Conclusions. Diabetes risk is increased by high waist circumference, but does not continue to increase with waist circumference, whereas in the case of BMI the risk gradually increases. BMI influences blood pressure more than waist circumference does.